Comparison of varus malalignment in unstable extracapsular proximal femur fracture between proximal femoral nail antirotation (PFNA) and proximal femoral locking plate (PFLCP) : a retrospective study - Lee, Mohammad Faizal Nikman (2017)
Unstable fractures of proximal femur of the pertrochanteric and subtrochanteric region are challenging injuries due to the high loads transmission across the affected part of the bone to the hip joint. The selection of the implants remained controversial but many studies favouring intramedullary implants for fractures’ fixation. The nature of the bone with strong muscular action with high compressive forces acting medially are responsible for intraoperative and postoperative complications and difficulties. Varus malalignment is one of the commonest complication found in proximal femur fractures. This study was done to evaluate the incidence of varus malalignment in unstable extracapsular proximal femur fracture. METHODS: 60 patients with closed unstable fracture of proximal femur involving pertrochanteric and subtrochanteric region were subjected into 2 groups of fixation and retrospectively evaluated. 30 patients each for proximal femoral nail antirotation (PFNA) and proximal femoral locking plate (PFLCP) group were operated. Incidence of varus malalignment immediately post operation, quality of fracture’s reduction immediately post operation and implant’s sustainability of fracture’s reduction at 6 months post operation were analyzed for both groups. RESULTS: Immediately after fracture’s fixation, incidence of varus malalignment was higher in PFLCP group (23.3%) compared to PFNA group (13.3%). However the quality of fracture’s reduction immediately post operation and implant’s sustainability of fracture’s reduction at 6 months between both implants were not statistically significant. CONCLUSIONS: PFLCP offered comparable result as PFNA for osteosysnthesis of unstable extracapsular proximal femur fracture in term of varus malalignment on immediate and 6 months post operation.